As revistas pedagógicas paulistas e as orientações para o ensino de aritmética nos primeiros anos escolares: um estudo quali-quantitativo (São Paulo, 1890-1920) - Gomes, Victor Hugo De Lemos [UNIFESP] (2020)
Objective: To investigate in the São Paulo Pedagogical Magazines which pedagogical orientations for the primary school mathematics teacher from 1890 to 1920. Methodology: as a research methodology, a content analysis was used, the work was divided into four stages: pre-analysis; list and categorization; information processing; and inference. Thirty-three arithmetic articles published in the period 1890-1920 were used in the research. The articles were treated with digital image processing and treatment using statistical calculations from software called IRAMUTEQ for further analysis, such as: Descending Hierarchical Classification, Similitude Analysis and Word Cloud. Results: From the quantitative analyzes, the qualitative inferences allowed to characterize the orientations for the teachers who teach arithmetic in the early years, elaborating a kind of “anatomy of the classes”. In this anatomy of the classes, elements such as: disciplinary field, teaching methods, teacher's actions, teaching stages, examples and exercises are explicit. In addition, we were able to identify magazines and authors most cited in the analyzed period.